TINJAUAN ATAS PENGAKUAN PENDAPATAN DAN BEBAN PADA CV. CARAKA USAHA MANDIRI - Paryati, Retno; Sukmawati, Gisella Putri (Journal of Economics, Accounting, Tax, and Management (JECATAMA), 2024)
This study aims to determine the recognition of income and expenses at CV. Caraka Usaha Mandiri. The method used in this research uses descriptive, comparative methods with a qualitative approach. The data collection technique was carried out by interview, literature research, and field research. The data collected was analyzed by means of data reduction, data presentation, and conclusion drawing. The results showed that the revenue and expense recognition of CV. Caraka Usaha Mandiri derived from the sale of goods is in accordance with SAK ETAP by using the accrual basis method, measuring income and expenses in accordance with the fair value of payments received, and presented in the profit and loss financial statements and balance sheets.